Sistem Pendeteksi Keberadaan Nelayan Menggunakan GPS Berbasis Arduino - I Gusti Made Ngurah Desnanjaya; I Made Aditya Nugraha; Samsul Hadi (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2021)
Global Position System (GPS) is a navigation system that can provide information from a device related to it from satellites. The related device is called a GPS receiver. Information obtained includes, among others, the latitude and longitude positions. This latitude and longitude information can tell the position of an object from the satellite. In this research, a search tool with Arduino-based GPS was made. What is needed to be able to find fishermen is that a fisherman must be able to send latitude and longitude coordinates from the satellite, which will later be translated by a mobile application, namely the Google Map, where this application is able to translate numbers from latitude and longitude coordinates. To be able to send these coordinates, we need a tool that can capture the coordinates and then send them to the specified user. From the research results, it can be seen that searching for missing fishermen using GPS is easier to find and more efficient in terms of time.